A Prospective Clinical Study Investigating the Relationship between Periodontal Disease and the Progression of Chronic Kidney Disease in Renal Transplant Recipients - Pallavi Priya; Sakshi Raina; Manisha Pathak; Subhash Kumar; Parul Chhabra; Vaibhava Raaj; Hiroj Bagde (Wolters Kluwer Medknow Publications, 2024)
Background: Periodontal disease and chronic kidney disease (CKD) are both prevalent conditions with significant implications for public health. This prospective clinical study aimed to explore the potential relationship between periodontal disease and the progression of CKD in renal transplant recipients. Materials and Methods: A total of 150 renal transplant recipients with varying degrees of periodontal disease were enrolled in this study. Baseline periodontal assessments, including probing depth, clinical attachment loss, and bleeding on probing, were conducted. The estimated glomerular filtration rate (eGFR) was measured at baseline and followed up at regular intervals over 24 months. Participants were divided into groups based on the severity of periodontal disease for comparative analysis. Results: At baseline, the mean eGFR was 60.5 ± 10.2 mL/min/1.73 m2 in the mild periodontal disease group, 58.3 ± 9.8 mL/min/1.73 m2 in the moderate periodontal disease group, and 55.7 ± 8.5 mL/min/1.73 m2 in the severe periodontal disease group. Over the 24-month follow-up period, participants with severe periodontal disease experienced a significant decline in eGFR compared to those with mild or moderate periodontal disease (P < 0.05). In addition, individuals with severe periodontal disease exhibited a higher incidence of CKD progression, defined as a decline in eGFR greater than 10% from baseline. Conclusion: This prospective clinical study suggests a potential association between severe periodontal disease and the progression of CKD in renal transplant recipients.